Evaluation of the role of CCR2 and CCR5 receptors in macrophage migration and alveolar bone repair outcome in mice - Fonseca, Angélica Cristina (2017)
Macrophages play important roles in bone repair, including the control of immune response and inflammation, and regulating the transition between granulation tissue to osteogenesis and formation of new bone after an injury. In this context, chemokine receptors, such as CCR5 and CCR2, seems to be key players in the chemotaxis of monocytes/macrophages to sites of tissue injury. The objective of this project is investigate simultaneously the role of CCR2 and CCR5 receptors in the cell migration and its subsequent impact on the alveolar repair process in mice. Mice C57BL/6 WT and CCR5KO, eight weeks old, were submitted to extraction of the right upper incisor and distributed in groups (N=5) control and treated with the antagonist for CCR2 (RS504393, 2mg/kg/24h), in order to allow of the blockage analysis individually or simultaneously of the receptors. Samples were collected in the 0h, 7d, 14d and 21days post extraction periods, and analyzed by micro-computed tomography (CT), histological analyzes (histomorphometry, immunohistochemistry and birefringence analysis), as well as molecular analysis by means of PCRArray for quantification of different markers involved in the repair process. Immunohistochemical analysis shows that CCR2 and CCR5 receptor blockade did not significantly influence the migration of monocytes/macrophages to alveolar bone repair. A similar pattern can be observed in MicroCT and in microscopic analyzes that do not demonstrate major changes in the parameters representatative of bone healing. On the other hand, molecular analyzes demonstrated that the simultaneous inhibition of CCR2 and CCR5 (CCR5KOantiCCR2 group) resulted in a a significantly higher mRNA expression of extracellular matrix markers (COL2A1 and MMP9), some bone markers (DMP1 and RANKL), FGF1 as well as IL-6 expression and decreased expression of growth factors (TGFb1 and VEGF), as well as RUNX-2 and cytokines (IL-10 and TNF-) when compared to WT-C. Therefore, we conclude that, although CCR2 and CCR5 receptor blockade result in significant modulation of of growth factors, proinflammatory cytokines and osteoclastogenic factors expression, there are no significant differences in the control of macrophage migration as well as in the subsequent bone repair outcome.